Housing and change: Women and progress in Givat Faradis - Levin, Iris; Kallus, Rachel (Hagar: Studies in Society and Culture, 2009)
This paper discusses the ramifications of "progress" as a generator of change in a traditional society. We investigated Givat Faradis, the new neighborhood adjacent to Faradis, a traditional Israeli-Palestinian town. We present interviews and discussions with two Israeli-Palestinian women as a basis for examining ambiguities and nuances in interpreting concepts of development, tradition and change. In the literature on Middle Eastern and Muslim societies, tradition is frequently represented as oppressive, severely curtailing women’s freedom, while change deriving from development and modernization is perceived as positive and constructive. Our findings seem to indicate that rigid adherence to tradition may sometimes, inadvertently, allow the rebellion inherent to development and progress; that change can be seen in and achieved through tradition in many different forms; and that it is perhaps becoming more possible to mitigate the deeply rooted schism between traditional and modern mores.